Exploring Secondary School English Teachers’ Knowledge of the Genre-Based Approach: Insight into Concept and Implementation - Fitri, Auliana; Setyarini, Sri; Purnawarman, Pupung (Universitas PGRI Semarang, 2026)
The Genre-Based Approach (GBA) has been widely implemented in national curricula to support students’ writing development through the scaffolded stages of the Teaching and Learning Cycle. Despite its prominence, limited research has explored teachers’ understanding of GBA from both conceptual and practical perspectives. This descriptive qualitative study aims to investigate how four Indonesian secondary school English teachers understand the principles and implementation of GBA in teaching writing. The participants were purposefully selected from junior and senior high schools and represented varied levels of teaching experience as well as different degrees of exposure to formal GBA training. This variation allowed for a comparative understanding of how training and experience shape teachers’ interpretations and classroom use of GBA. Data were collected through semi-structured interviews that explored teachers’ conceptual knowledge of GBA, their understanding of the Teaching and Learning Cycle, instructional strategies across its stages, and assessment practices in genre-based writing instruction. The findings reveal that teachers who had received formal GBA training demonstrated stronger theoretical understanding of how to implement the Teaching and Learning Cycle systematically. In contrast, teachers without formal training tended to rely more on experience-based practices, often focusing on surface features of texts. Although all participants recognized the benefits of GBA for students’ writing development, they also reported common challenges, including limited instructional time, diverse student proficiency levels, and restricted teaching resources. These findings highlight the importance of ongoing professional development and sustained institutional support to enable teachers to implement GBA more effectively in secondary school classrooms.